(untitled) (Proximus Journal of Sports Science and Physical Education, 2025)
This research aims to design tests to measure skill and cognitive performance in wrestling. A descriptive approach was adopted, using survey and correlation techniques, given its suitability to the nature of the research problem. The research population included all 30 third-year students in the College of Physical Education and Sports Sciences at the University of Misan. A comprehensive enumeration method was used to determine this sample for the academic year 2023-2024. The researcher used the statistical package SPSS24. The study concluded that the tests for measuring skill and cognitive performance in wrestling are characterized by their ease of application and low cost, in addition to not requiring the use of many devices or tools. They also efficiently measure the purposes for which they were designed, enabling teachers to accurately evaluate students. The study recommended the importance of adopting these tests in evaluating students in colleges of physical education and sports sciences. It also emphasized the need to conduct similar studies on larger samples or in other fields related to wrestling and sports in general.